Evaluation of Risk Management in the Ministry Interior of Iraq According to the Standards (ISO 31000: 2018) - Alaa Hussein *, Hasan; Kamel Jawad, Maha (Journal of Economics and Administrative Sciences, 2024)
The idea of the research is to evaluate the extent to which risk management is applied in the work of the departments and formations of the Iraqi Ministry of Interior, and this is done by comparing the actual reality of the Ministry’s work with the international standard for risk management, which is (ISO 31000:2018), as the problem of the research centers is the Ministry’s lack of a clear definition that is clear about how risks are managed, and this can be seen after reviewing the strategic and annual plans, which showed that this topic was not included in them. In contrast, the research aims to determine the actual reality of the Ministry’s work in institutional risk management by comparing this reality with the provisions of the ISO standard 31000:2018. To determine the gap and the level of application, the researcher relied on the Ministry’s strategic plan to determine the research sample, which is divided into three axes, namely (administrative, service, and security), where three departments were chosen, namely (the Directorate of Financial Resources, the Directorate of Civil Defense, the Leadership Border Forces), and the checklist was designed based on the provisions of the standards used Equations (Weighted arithmetic mean and Percentage of conformity(, through which the extent of conformity with the requirements of the standards can be known. After conducting field tours, interviews, and reviewing the records and documents of the departments, the inspection lists were filled out, and the gap was calculated, which was (60%), which is a relatively large gap. Paper type: research paper